Diffusional effects of excellence education on the institution as a whole. Issue 1 (2nd January 2021) - Kolster, Renze
ABSTRACT: Having found that excellence education in Dutch higher education institutions can function as a testing ground for educational innovations, we ask the questions: Are 'excellence education' teaching methods diffused towards courses in regular study programmes? Are organisational structures affected? And are there noticeable external effects? And through which processes are the rest of the organisation impacted? We study these questions using qualitative empirical insights of five case study higher education institutions. We see some educational, organisational, and external diffusional effects. In education, teachers indicated to experiment with educational content in excellence education, after which they implemented this in regular study programme courses too. On the organisational level, a prominent effect was the creation of new relationship structures, particularly amongst teachers involved in excellence education. Commonly heard external effects included heightened reputation and visibility of the institution due to offering excellence education. Reflecting on the diffusion process, we observe that the diffusion mainly happens through teachers who are involved in excellence and regular education. Policy instruments are rarely specifically designed to create diffusional effects. Consequently, steering of the diffusion of innovations by inter alia university management appears not to happen often.